Knockdown of Splicing Complex Protein PCBP2 Reduces Extravillous Trophoblast Differentiation Through Transcript Switching - Georgiadou, Danai; Boussata, Souad; Keijser, Remco; Janssen, Dianta A. M.; Afink, Gijs B.; van Dijk, Marie (Frontiers in Cell and Developmental Biology, 2021)
Mutations in the LINC-HELLP non-coding RNA (HELLPAR) have been associated with familial forms of the pregnancy-specific HELLP syndrome. These mutations negatively affect extravillous trophoblast (EVT) differentiation from a proliferative to an invasive state and disturb the binding of RNA splicing complex proteins PCBP1, PCBP2 and YBX1 to LINC-HELLP. In this study, by using both in vitro and ex vivo experiments, we investigate if these proteins are involved in the regulation of EVT invasion during placentation. Additionally, we study if this regulation is due to alternative mRNA splicing. HTR-8/SVneo extravillous trophoblasts and human first trimester placental explants were used to investigate the effect of siRNA-mediated downregulation of PCBP1, PCBP2 and YBX1 genes on the differentiation of EVTs. Transwell invasion assays and proliferation assays indicated that upon knockdown of PCBP2 and, to a lesser extent, YBX1 and PCBP1, EVTs fail to differentiate towards an invasive phenotype. The same pattern was observed in placental explants where PCBP2 knockdown led to approximately 80% reduction in the number of explants showing any EVT outgrowth. Of the ones that still did show EVT outgrowth, the percentage of proliferating EVTs was significantly higher compared to explants transfected with non-targeting control siRNAs. To further investigate this effect of PCBP2 silencing on EVTs, we performed whole transcriptome sequencing (RNA-seq) on HTR-8/SVneo cells after PCBP2 knockdown. PCBP2 knockdown was found to have minimal effect on mRNA expression levels. In contrast, PCBP2 silencing led to a switch in splicing for a large number of genes with predominant functions in cellular assembly and organization, cellular function and maintenance, and cellular growth and proliferation and the cell cycle. EVTs, upon differentiation, alter their function to be able to invade the decidua of the mother by changing their cellular assembly and their proliferative activity by exiting the cell cycle. PCBP2 appears to be a paramount regulator of these differentiation mechanisms, where its disturbed binding to LINC-HELLP could contribute to dysfunctional placental development as seen in the HELLP syndrome.